Using natural experiments to evaluate population health interventions: new Medical Research Council guidance. Issue 12 (10th May 2012) - Craig, Peter; Cooper, Cyrus; Gunnell, David; Haw, Sally; Lawson, Kenny; Macintyre, Sally; Ogilvie, David; Petticrew, Mark; Reeves, Barney; Sutton, Matt; Thompson, Simon
Abstract : Natural experimental studies are often recommended as a way of understanding the health impact of policies and other large scale interventions. Although they have certain advantages over planned experiments, and may be the only option when it is impossible to manipulate exposure to the intervention, natural experimental studies are more susceptible to bias. This paper introduces new guidance from the Medical Research Council to help researchers and users, funders and publishers of research evidence make the best use of natural experimental approaches to evaluating population health interventions. The guidance emphasises that natural experiments can provide convincing evidence of impact even when effects are small or take time to appear. However, a good understanding is needed of the process determining exposure to the intervention, and careful choice and combination of methods, testing of assumptions and transparent reporting is vital. More could be learnt from natural experiments in future as experience of promising but lesser used methods accumulates.